Social Media and its Impact on Youth of Kathmandu Valley - Gnawali, Achyut (Saptagandaki Journal, 2020)
Social media is a worldwide networking platform that serves as a medium for the people to connect and communicate with each other and for the youth to explore the world. The objective of this study was to examine the social media factors affecting on the youths of Kathmandu valley. The study is based on 408 respondents from Kathmandu valley. To achieve the purpose of study, structured questionnaire was prepared. Inferential statistics were used to make proper analysis. The result shows that types of social media used and availability of social media are positively correlated with impact on youth. The regression result shows that the beta coefficients for types of social media used and availability of social media are positive and significant with impact on youth. The result also shows that the beta coefficient for psychology of social media users is negative with impact on youth.